Trinity Cathedral, Trinidad - (:unkn) unknown (Wilson Ltd., Trinidad, 2010)
Image depicts a view of the Trinity Cathedral, located in the capital city of Port of Spain, Trinidad, in the Republic of Trinidad and Tobago. The cathedral is bounded by Frederick Street on the east, Abercromby Street on the west, Hart Street on the north and Queen Street on the south. This is a view of the building from its Queen Street entrance, looking north.
Colour: Shades of green, gray, blue, yellow, purple and white; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings